The educational and educational importance of virtual historical museums theoretical vision-- (Journal of Misan Researches, 2024)
Museums are a cultural and educational institution, as they display collections of cultural property to preserve them and benefit from them in various fields of education and in the dissemination of culture and science. It is also the place where gifts, luxurious and precious things, artistic monuments, cultural property, valuables, and rare pieces were collected that souls long to see and look forward to contemplating and admiring. Active in the process of education and teaching, especially in teaching history and its various concepts. Many of the books on methods of teaching history contain many pages to talk about museums and their importance in the educational process and in teaching and learning as it is one of the sources of sensory knowledge that provides the learner with scientific information, facts, and educational and moral values.